A Retrospective Evaluation of Mean Platelet Volume and the Neutrophil-to-lymphocyte Ratio in Children with Chronic Urticaria - Mehmet Ali Duman; Hatice Duman; İlteriş Oğuz Topal; Hatice Nilgün Selçuk Duru (Galenos Yayinevi, 2019)
Aim:Recently, it has been reported that the mean platelet volume (MPV) and neutrophil-to-lymphocyte ratio (NLR) can be used as indicators of inflammation in various inflammatory diseases such as psoriasis, ankylosing spondylitis and ulcerative colitis. In this study, we aimed to assess MPV levels and NLR in children with chronic urticaria (CU) and to compare them with healthy controls.Materials and Methods:The cases of 46 children with CU [11 with inducible urticaria (IU) and 35 with chronic spontaneous urticaria (CSU)] admitted to our outpatient clinics, and 30 healthy children were evaluated retrospectively.Results:No statistically significant differences among the CU, CSU, and IU and the control groups were found in terms of NLR and MPV levels (p>0.05). The platelet counts in the CU, CSU, and IU and control groups were not statistically significantly different (p>0.05).Conclusion:We found that MPV levels and NLR were not different in children with CU, CSU, and IU and in healthy children. It seems that the MPV and NLR cannot be used as inflammatory markers of CU in children. We believe that further studies are required in this field.